Program Implementation Approaches to Build and Sustain Health Care Coordination for Type 2 Diabetes. Issue 2 (March 2017) - Fitzgerald, Tania M.; Williams, Pam A.; Dodge, Julia A.; Quinn, Martha; Heminger, Christina L.; Moultrie, Rebecca; Taylor, Olivia; Nelson, Belinda W.; Lewis, Megan A.
Background: As more people enter the U.S. health care system under the Affordable Care Act (ACA), it is increasingly critical to deliver coordinated, high-quality health care. The ACA supports implementation and sustainability of efficient health care models, given expected limits in available resources. This article highlights implementation strategies to build and sustain care coordination, particularly ones consistent with and reinforced by the ACA. It focuses on disease self-management programs to improve the health of patients with type 2 diabetes, exemplified by grantees of the Alliance to Reduce Disparities in Diabetes. Method: We conducted interviews with grantee program representatives throughout their 5-year programs and conducted a qualitative framework analysis of data to identify key themes related to care coordination. Results: The most promising care coordination strategies that grantee programs described included establishing clinic–community collaborations, embedding community health workers within care management teams, and sharing electronic data. Establishing provider buy-in was crucial for these strategies to be effective. Discussion: This article adds new insights into strategies promoting effective care coordination. The strategies that grantees implemented throughout the program align with ACA requirements, underscoring their relevance to the changing U.S. health care environment and the likelihood of further support for program sustainability.